Angels in the service of God and man - Chrapusta, Adam; Skoczeń , Ireneusz (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
Abstract: The article discusses the tasks and role of angels in human life and their mission in the service of God and man. It introduces their nature and significance and draws attention to their presence in the life of man and the Church. It rejects the image of "media angels", heroes of outer space, fighting against good and evil possessing a secret power which they acquire from the energy of the universe. The text is also a concise study based on Scripture and gives examples of the interventions of God's messengers at key moments in human history. In order to achieve this, it was necessary to analyse the texts of Scripture in which the content about angels is recorded and to draw on Tradition. The material gathered in this way had to be critically analysed in order to obtain a concise picture and outline of the topic of angels. Above all, it was a question of sources and a method of understanding the nature of angels. Following the analysis, it can be multiply concluded that angels are spirits created by God. The authors of the text dissociate themselves from the image of angels perpetuated in pop culture as cupids, spirits and protectors in various life situations. The text is intended to be an encouragement for Christians to open themselves anew to the richness of the spiritual world created by God, while at the same time being an aid to evangelisation.